Regioselectivity Change in the Organocatalytic Enantioselective (3+2) Cycloaddition with Nitrones through Cooperative Hydrogen‐Bonding Catalysis/Iminium Activation. Issue 12 (7th February 2017) - Prieto, Liher; Juste‐Navarro, Veronica; Uria, Uxue; Delso, Ignacio; Reyes, Efraim; Tejero, Tomas; Carrillo, Luisa; Merino, Pedro; Vicario, Jose L.
Abstract: The reaction of nitrones with enals through iminium activation can be modulated by using cooperative hydrogen‐bonding catalysis to induce the participation of a nitrone ylide (C‐N‐C) instead of the classical C‐N‐O dipole. As a consequence, N ‐hydroxypyrrolidines are obtained, rather than the expected isoxazolidines. The reaction proceeds smoothly and high enantioselectivities are observed in all cases. By using the appropriate substrate, polysubstituted pyrrolidines incorporating quaternary stereocenters can be efficiently prepared. Abstract : Thank you for your cooperation : Cooperative hydrogen‐bonding catalysis/iminium activation enables chemoselectivity reversal for the enantioselective (3+2) cycloaddition of nitrones with enals, promoting the participation of a nitrone ylide (C‐N‐C) instead of the classical C‐N‐O dipole.